DASAR NEGARA DAN TAQIYYAH POLITIK PKS - Abu Rokhmad (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2014)
This article studied about the relationship between Partai Keadilan Sejahtera (PKS/the Prosperous Justice Party) and Pancasila as the state’s philosophy. PKS didn’t have the experience of the struggle of Indonesian independence and the difficult period of the Pancasila formulation. PKS was born after Pancasila convinced as the national agreement. The political attitude of PKS to Pancasila as the state’s philosophy is still indistinct. PKS viewed as political party that hide their truly intent: between receiving Pancasila and implementing islamic shari’ah. The aspiration of implementing islamic shari’ah has been concealing in vision and mission as well as in the heart of PKS’s cadres. The aspiration will be done by peaceful and constitutional ways.